Management of Radiation-Induced Proctitis - Frank H Anderson; Lecheng Zeng (Canadian Journal of Gastroenterology)
The acute form of radiation intestinal injury is usually transient and self-limited, while chronic injury is permanent and progressive, and its management is unsatisfactory. As reported recently, however, several treatment options are available to control symptoms reasonably in most cases. Some approaches are of particular interest due to their efficacy, availability and simplicity. More clinical evaluations are required to confirm this initial enthusiasm.